(3GdehGLgI GdLfGFjI dLQGFe GdEJLGQ HGdHTQ (B: s (3OQGSI ai GdbGfhf GdYeGfi h GdebGQf (B/ s - (3CMeO Hf UGdM Hf fGUQ GdHQhGfis; (3TQja SjO cGed s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3CUHMJ LQjeI GdEJLGQ HGdHTQ XGgQI YGdejI Jbhe HgG LeGYGJ ELQGejI YHQ GdOhd(B: (3h bO ESJZdJ Jdc GdLeGYGJ XQha eLJeYjI eKd XGgQI GdYhdeI h GdabQ GdeObY ai GdcKjQ ef GdOhd h EfJTGQ GdaSGO Hjf GdLgGJ GdMchejI ddJQhjL dLQGFege(B: (3h jTcd GdEJLGQ HGdHTQ YfUQkG QFjSjkG ai CfTWI GdefXeGJ GdELQGejI h GdJTcjdGJ GdYUGHjI(B: (3h JONd LQjeI GdEJLGQ HGdHTQ Vef eaghe GdLQjeI GdefXeI(B: (3MjK Jbhe YUGHGJ EMJQaJ GdELQGe h LYdJ GdLQjeI eMhQ fTGWgG GdPi JeGQSg(B: (3h eUOQ ONdgG(B: (3HGdEVGaI Edi Pdc(B: (3aEf YUGHGJ GdLQjeI GdefXeI GdJi Jba hQGA XGgQI GdGJLGQ HGdHTQ ZGdHG eG Jchf eJYOOI GdLfSjGJ ef MjK ghjI CYVGFgG h fWGb YedjGJgG(B: (3h HGdJGdi(B: (3aEf GdeTcdI HGdaYd eTcdI YGdejI(B. (3h LQGFe GdGJLGQ HGdHTQ h Gf GNJdaJ CTcGdgG h CfhGYgG h eYOdGJ EQJcGHgG ef OhdI Edi CNQi(B: (3JHYG dXQha cd OhdI(B: (3aEfgG MJekG JDKQ Ydi GdOhd GdeUOQI h GdeSJbHdI dgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2015(3, bSe GdbGfhf GdLfGFis
(3HHdjhLQGajG(B: (3UaMGJ (B307-325s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFi s; (3GdGJLGQ HGdHTQ aj GdbGfhf GdYeGfj s; (3GdGJLGQ HGdHTQ aj GdbGfhf GdSYhOj s; (3GdGJLGQ HGdHTQ aj GdbGfhf GdGeGQGJj s; (3GdGJLGQ HGdHTQ aj GdbGfhf GdchjJjs; (3GdGJLGQ HGdHTQ aj GdbGfhf GdHMQjfj s; (3JYQja GdGJLGQ HGdHTQ aj GdbGfhf GdbWQjs; (3GdGJLGQ HGdHTQ aj GdbGfhf GdeUQj s; (3GdGJLGQ HGdHTQ aj GdbGfhf GdCQOfj s; (3GdGJLGQ HGdHTQ aj GdbGfhf GdYQGbj s; (3GdGJLGQ HGdHTQ aj GdbGfhf GddHfGfj s; (3LQGFe GdEJLGQ HGdHTQ s; (3GdaFGJ GdeSJgOaI ef GdGJLGQ HGdHTQ s; (3GSJZdGd GdGWaGd s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs